Pengaruh Pembelajaran Matematika Menggunakan Model Learning Cycle Terhadap Hasil Belajar Siswa Pokok Bahasan Barisan Dan Deret Kelas XI IPA SMAN 1 Kerinci - Sapiah Sapiah (Universitas Batanghari Jambi, 2021)
The purpose of writing this research is to determine the learning outcomes of mathematics learning on the subject matter of the language of sequences and series by using the learning cycle learning model before using the learning cycle learning model (Lecture learning model). This study uses quantitative research methods with an experimental approach. The population of this research is all students of class XI IPA using purposive sampling technique, the class that will be sampled in this study is seen from the level of ability possessed by each student in understanding the subject matter of sequences and series, where the sample is 25 control class students, and 25 experimental class students. There are three stages of data collection techniques, namely the preparation stage, the implementation stage and the final stage. The analysis of the instrument test carried out in this experimental study used a test of validity and reliability, a test of the level of difficulty of the test items, and a test of discriminating power. While the technique to analyze the data using normality test, homogeneity test, and hypothesis testing using t-test. The results of this study indicate that there are differences in student learning outcomes on the subject matter of sequences and series before using the Learning Cycle learning model and after using the Learning Cycle learning model. This can be seen by using the t-test part of the t-test for Equality of Means, the sig value is known. (2 tailed) of 0.000 < 0.05.